The Effect of Provision of Right and Left Mobilization Against Prevention of Decubitus Ulcers in Stroke Patients - Tenriwati; Asnidar (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2017)
In the world, the number of stroke sufferers who experience pressure ulcers from year to year has increased. Based on data from the World Health Organization (WHO) in 2008 the number of stroke sufferers hospitalized with decubitus ulcers 3-10% and 2.7% have the opportunity to form new ulcers. The incidence of decubitus ulcers in Indonesia is very high compared to other countries. The purpose of this study was to determine whether there is an effect of giving the right and left oblique mobilization to stroke patients in the inpatient. This study uses a quasi-experimental design with a pre-test and post-test approach only with control groups. The collected data were analyzed by Wilcoxon's Marginal Homogeneity test. The results of the analysis in the intervention group were p values ​​0.046 (<0.05) which showed that there was an effect of giving the right and left oblique mobilization to the prevention of pressure sores in stroke patients, the results of the analysis in the control group were p values ​​= 0.003 (<0.05) ) which shows there is no effect of giving the right and left sloping mobilization to the incidence of pressure sores in stroke patients and the results of the analysis in the intervention group and the control group obtained p-value of 0.004 (<0.05) which indicates there is a significant difference in the proportion of ulcer events decubitus in respondents who were given right and left oblique mobilization with respondents who were not given right and left oblique mobilization. The suggestion from researchers is that this research can add to the treasury of science and can be used as reading material in the development of science, and become information material for health workers for the future daily observation and prevention measures for pressure ulcers can be increased again.